Mexico : Water Public Expenditure Review - World Bank (Washington, DC, 2013)
Mexico has critical and urgent water related problems including the overexploitation and contamination of surface water and groundwater resources in the regions where most of the people reside and where the great majority of the Gross Domestic Product, or GDP is generated. Groundwater overexploitation is perhaps the most serious water resources management issue. About 100 aquifers in the central and northern part of the country are being overexploited, with water tables dropping 1 to 4 meters per year. In some areas, essentially all sectors depend on groundwater, and the unsustainable water use regimen will constrain economic development and have serious social impacts. The poor often suffer the most, because they are less able to deal with the added costs associated with falling water tables and water pollution. Water issues are both very complex and very important in Mexico, because they sit at the conjunction of economic development, public finance, infrastructure investment, environmental sustainability, and social justice. They are linked to public finance in three ways, raising resources, providing resources for investment and operations, and setting fees that affect the incentives for using water. The decisions about water investment have a lasting physical impact on what happens with water, as well as major social impacts. The scarcity of water in many parts of the country means that sometimes more water for one sector results in less water (and a different development path) in another sector and for the environment. The national patrimony relating to the ecosystem and groundwater often ends up last in line, as everyone generally agrees on their importance but objects to having his allocation of water or fiscal subsidy be reduced or to paying for wastewater treatment. Finally, making water and water services available equitably to households is a key element in the social justice to which Mexicans aspire. The report aims to integrate the views of the water sector through these different lenses, and to suggest how to improve the management of the sector and thus to make decisions more coherent.